2024
DOI: 10.3390/land13020200
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Agricultural Expansion in Degraded Pasture Lands in Brazil Based on Geospatial Databases

Édson Luis Bolfe,
Daniel de Castro Victoria,
Edson Eyji Sano
et al.

Abstract: Important public and private initiatives to map agricultural lands and natural resources have been carried out in Brazil to support land use planning. Some studies indicate that Brazil still has up to 109.7 million hectares of cultivated pastures with some level of degradation, representing around 60% of the total pasturelands, estimated at 177 million hectares. This study aimed to gather, process, and analyze publicly available databases to generate quantitative and spatial information about the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In ecosystems like the Cerrado, characterized by a prolonged dry season and a naturally less vigorous vegetation, due to soil and climate conditions, biological degradation is the predominant form [5]. Various pasture management strategies and techniques exist to recover or renew degraded pastures in the Brazilian savanna, with costs increasing in direct proportion to degradation levels [5,[9][10][11]. In our study, this observation validates Our study, therefore, has identified suitable periods for data acquisition, notably the transition from the rainy to the dry season (May to June) and the beginning of a new seasonal cycle in October after the initial rainfall events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ecosystems like the Cerrado, characterized by a prolonged dry season and a naturally less vigorous vegetation, due to soil and climate conditions, biological degradation is the predominant form [5]. Various pasture management strategies and techniques exist to recover or renew degraded pastures in the Brazilian savanna, with costs increasing in direct proportion to degradation levels [5,[9][10][11]. In our study, this observation validates Our study, therefore, has identified suitable periods for data acquisition, notably the transition from the rainy to the dry season (May to June) and the beginning of a new seasonal cycle in October after the initial rainfall events.…”
Section: Discussionmentioning
confidence: 99%
“…This interest is fueled by the recognition that well-managed and productive pasturelands have the potential to enhance carbon sequestration and reduce carbon emissions [6][7][8]. Another compelling reason for mapping these areas is to devise strategies or policies aimed at the potential conversion of degraded pastures into reforested areas or agricultural land [8,9]. For example, through effective management of degraded pastures, these areas can be transformed into soybean fields, contributing to increased crop production without causing deforestation or clearing of native vegetation in both the Cerrado and Amazon biomes.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bolfe et al (2024) [43], approximately 110 million ha of pasture exhibit some level of degradation, representing about 60% of the total. Of these, 28 million ha are moderately or severely degraded but are situated on land suitable for crop production (Figure 2).…”
Section: Sustainable Intensification: the Path To Brazilian Low Carbo...mentioning
confidence: 99%
“…In response, there is growing appeal for the sustainable intensification of Brazilian agriculture and beef farming in particular. Bolfe et al (2024) [43] argue that converting 28 million ha of degraded pasture, as encouraged by the National Programme for the Conversion of Degraded Pastures (MAPA, 2023) [42], could increase the total crop area by 35%, compared to the 2022/2023 crop season. Alternatively, recovering 30 million ha of pasture for improved beef farming would require an investment of USD 8.6 billion and could yield returns ranging from USD 440 million to USD 6.7 billion, depending on various beef price scenarios (Carlos et al, 2022) [47].…”
Section: Sustainable Intensification: the Path To Brazilian Low Carbo...mentioning
confidence: 99%
See 1 more Smart Citation